Understanding the Adoption and Perceptions of Generative AI in Higher Education: Insights from Undergraduate Science Students in FWU, Nepal - Ramesh Prasad Bhatta (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
Artificial intelligence tools, notably LLMs such as ChatGPT, are rapidly transforming higher education around the world. This study explores the perceptions of GenAI awareness, adoption, its perceived benefits, and limitations among undergraduate science students in Far Western University, Nepal. Cross-sectional quantitative research design has been adopted involving 91 undergraduate science students in an online survey using structured questionnaires. Data were analyzed using descriptive analysis and chi-square goodness-of-fit tests. The findings suggest that a relatively high number of participants had adopted GenAI and used ChatGPT most frequently. The respondents mainly used GenAI for educational purposes. However, various limitations have been found, which include affordability, lack of proper connection, worries about the accuracy of information, and use of mobile devices for GenAI tools' access. This study has brought out a major contradiction in GenAI adoption in developing countries in higher education where the level of student participation is high despite the structural and infrastructural constraints. The results are very significant in terms of providing baseline data from a less represented area in the world.